Pengaruh Good Corporate Governance dan Kualitas Audit Terhadap Pengungkapan Sukarela Laporan Tahunan Perusahaan Transportasi di BEI Tahun 2020-2022 - Putri, Dhea Amelya; Pertiwi, Dwi Ari (JFAS : Journal of Finance and Accounting Studies, 2024)
This study aims to determine the effect of Good Corporate Governance and Audit Quality on the Voluntary Disclosure of Annual Reports of Transportation Companies on the IDX in 2020-2022. The type of research used in this study is quantitative research. The data collection technique used in this study is using secondary data. The population of this studi is 27 companies and the sampling used in this study is purposive sampling so that 13 companies are obtained. Data analysis using the SPSS 20 software method. The results of this study show that Good Corporate Governance represented by managerial ownership does not effect voluntary disclosure of annual reports of transportation companies on the IDX in 202-2022, this is shown by a significant value of 0.142, meaning a significant value greater than 0.05. Audit quality affects voluntary disclosure of annual reports of transportation companies on the IDX in 2020-2022, this is shown by a significant value of 0.002, meaning a significant value is less than 0.05